ANALISIS PENGARUH KARAKTERISTIK BINTANG IDOLA IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK MIE INSTANT MEREK INDOMIE - Pujianti, 07.05.51.0145; Widyasari, Suzy (Students Journal of Economic and Management, 2012)
Advertising is the main source of information in decision making. Advertising activity is one of the main promotional tool that is often used to direct communications are persuaded to that is aim. Advertisements may use a lot of media, one is the television media. Celebrity endorser are widely used in magazine ads, as well as a TV commercial to support product. The ads Star (celebrity endorser) move as people are talking about a product that will influence the nature and behavior of consumers who refer to the products that it supports. This research aims to analyze the effect of visibility, credibility, attraction and the power Indomie purchasing decisions on student Unisbank in Semarang. Hypothesis is : Visibility, Credibility, Attraction and Power influential positive and significant to Purchasing Decision, as partially or simultanly.The population in this study are students of Unisbank, Semarang. The sample in this research is student Unisbank of 100 respondents. Type the data is the primary. A method of collecting data using a questionnaire. The techniceque analysis data used in this research is multiple regression. The result of this research showing that, visibility, credibility, attraction and power has significant and positive effect to purchasing decisions indomie as partially and simultanly. Key words : Visibility, Credibility, Attraction, Power and Purchasing Decision